Effects of Plyometric Training on Explosive and Endurance Performance at Sea Level and at High Altitude - Andrade, David Cristóbal; Beltrán, Ana Rosa; Labarca-Valenzuela, Cristian; Manzo-Botarelli, Oscar; Trujillo, Erwin; Otero-Farias, Patricio; Álvarez, Cristian; Garcia-Hermoso, Antonio; Toledo, Camilo; Del Rio, Rodrigo; Silva-Urra, Juan; Ramírez-Campillo, Rodrigo (Frontiers in Physiology, 2018)
Plyometric training performed at sea level enhance explosive and endurance performance at sea level. However, its effects on explosive and endurance performance at high altitude had not been studied. Therefore, the aim of this study was to determine the effects of a sea level short-term (i.e., four-week) plyometric training program on explosive and endurance performance at sea level and at high altitude (i.e., 3270 m above sea level). Participants were randomly assigned to a control group (n=12) and a plyometric training group (n=11). Neuromuscular (reactive strength index – RSI) and endurance (2-km time-trial; running economy [RE]; maximal oxygen uptake - VO2max) measurements were performed at sea level before, at sea level after intervention (SL+4wk), and at high altitude 24-h post SL+4wk. The ANOVA revealed that at SL+4wk the VO2max was not significantly changed in any group, although RE, RSI and 2-km time trial were significantly (p<0.05) improved in the plyometric training group. After training, when both groups were exposed to high altitude, participants from the plyometric training group showed a greater RSI (p<0.05) and were able to maintain their 2-km time trial (11.3 ± 0.5 min vs. 10.7 ± 0.6 min) compared to their pre-training sea level performance. In contrast, the control group showed no improvement in RSI, with a worse 2-km time trial performance (10.3 ± 0.8 min vs. 9.02 ± 0.64 min; p<0.05; ES= 0.13). Moreover, after training, both at sea level and at high altitude the plyometric training group demonstrated a greater (p<0.05) RSI and 2-km time trial performance compared to the control group. The oxygen saturation was significantly decreased after acute exposure to high altitude in the two groups (p<0.05). These results confirm the beneficial effects of sea level short-term plyometric training on explosive and endurance performance at sea level. Moreover, current results indicates that plyometric training may also be of value for endurance athletes performing after an acute exposure to high altitude.